EVALUATION OF WATER USE INTENSITY IN KHARKIV REGION - ЖУК, В. М. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy)
Conditions of use surface water in Kharkiv region. The features and nature of water use by the main sectors of the economy. Shows the structure of the main water companies. The estimation of wastewater quality categories for major water pollutants.